Rethinking state and border formation in the Middle East - Tejel, Jordi. (Edinburgh)
viii, 381 sayfa
Keywords: “Reinterprets the making of the Turkish-Syrian-Iraqi borderlands from a decentred and connected perspectiveAnalyses the violence and forced displacement in the borderlands of the post-Ottoman Middle EastExamines the contribution of border populations to the making of the history of the borderlands, nation-states and the region as a wholeCovers the borderlands stretching between Turkey, Syria, and Iraq while paying attention to border variations Turkey-Syria/Turkey-Iraq/Syria-IraqUtilises theoretical and methodological debates in borderlands and mobility studies, as well as social, environmental and transnational historyWhile the wars in Iraq, Syria, Libya and Yemen, alongside the establishment of the so-called “Islamic Caliphate“ have brought the debate about the crisis of the territorial nation-state in the Middle East once again to the fore, this issue cannot be simply understood as the logical consequence of either an imported political construction or the purported artificiality of Middle Eastern borders. Instead, the process of state formation in the region has been a complicated course that involved different institutional traditions, managing societies marked by varying degrees of political loyalty to central power, and dealing with colonial interference. Rethinking State and Border Formation in the Middle East seeks to disentangle some of these complexities by proposing both a decentred and dialectic approach. Taking its cue from the bourgeoning field of borderland studies and a variety of historical sub-disciplines, this monograph pays attention to the circulation of people, goods, diseases and ideas as well as to the everyday encounters between a wide range of state and non-state actors in the borderlands laying between Turkey, Syria and Iraq. The goal is to provide a much more holistic yet finely-grained understanding of the formation of the territorial state in the interwar Middle East” --